A comparative study of alternative rice production systems in Laos - Montha Narisak; Cowell, P. A.; Singh, Gajendra; Goede, J.H. de; The Mekong (Bangkok : Asian Institute of Technology, 1976)
This study is an investigation,of the production efficiency and the possible labour capacity per crop of alternative rice production systems project farm, traditional paddy farm and upland rice farm, at the farm level, It is a cross-sectional study at the micro-level of rice production in Laos with reference to the Tha Ngon Agricultural Development Project and the traditional farms in the vicinity, It is a real and practical approach in identifying the actual input-output factors at every stage of the production line, a It provides basic data and information for further studies in developing simulation model of alternative rice production systems, Also it draws up some guidelines for a technological change in the production line, It characterises the effects of technological change on the labour performance and on the cultural and social system of farmers.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand
Thesis (M.Eng.) - Asian Institute of Technology, 1976
Keywords: Rice -- Laos